GAIN-SCHEDULING OPTIMISATION OF PITCH HOLD MODE BASED ON GENETIC ALGORITHMS - Nadsadna, Оlga (Proceedings of National Aviation University (archive), 2015)
This paper presents an algorithm that was developed to select the best controller gains. The method is based on solving robust optimization problem for family of gain-scheduled PID-controllers. Parametric robust optimization provided by using genetic algorithm approach. This technique is useful to obtain flexibility and robustness in the controller automatic design.